A New Japan Volcanological Database - Fujita, Eisuke; Ueda, Hideki; Nakada, Setsuya (Frontiers in Earth Science, 2020)
For the purpose of the development of volcanology and practical application to volcanic hazard mitigation, we are conducting a new project named the Integrated Program for Next Generation Volcano Research and Human Resources Development (INeVRH). This project consists of 4 themes focusing on observation, forecasting, countermeasures and data sharing system. Data sharing system is named the Japan Volcanological Data Network (JVDN), which will be a platform to combine observation, prediction and countermeasure data to give information for the judgement at branch nodes of event tree for volcanic crises.